Development of administrative creativity in the framework of high containment management practices - Ayad Fadhil Mohsin, Suzan Abdulghani Ali, Abdulsattar Salim Auadh, (Opción, 2019)
The aim of this research is to identify the relationship between management practices and higher management strategies. In order to using the descriptive analytical method as a research method, the research was conducted on a sample of (290) individual working in the General Company for Electrical Industries in Iraq. As a result, the degree of individuals’ perception of management practices in the high containment above the medium, and individuals' awareness of management innovation strategies was high. The study concluded that there is a significant positive relationship between some management practices and higher management strategies.